Integrasi ChatGPT dalam Pembelajaran Biologi: Tantangan dan Peluang di Perguruan Tinggi - Citraningrum, Mivtha; Rophi, Apriani Herni; Haka, Nukhbatul Bidayati (STKIP HARAPAN BIMA, 2026)
This study aims to examine the challenges and opportunities of integrating ChatGPT into Biology learning through a qualitative descriptive approach. Data were collected through participant observation, in-depth interviews, and literature review, and were analyzed thematically. The findings indicate that the use of ChatGPT as an instructional support tool has both positive and negative impacts. Students reported that it helped them understand complex biological concepts through simpler and more adaptive explanations. However, there is a tendency for students to become dependent on ChatGPT in completing assignments without engaging in independent analysis. Lecturers also highlighted concerns regarding academic integrity, such as plagiarism and the use of AI without proper attribution. Overall, ChatGPT has the potential to enhance learning if used purposefully and supported by adequate digital literacy. Its integration should be positioned as a pedagogical support tool rather than a substitute for teachers. Key challenges include technological dependency, academic ethical issues, and limited digital literacy. Continuous evaluation is necessary to maximize benefits and minimize risks in Biology education.